2022
DOI: 10.3390/app12126042
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Psychology of Social Engineering-Based Cyberattacks and Existing Countermeasures

Abstract: As cybersecurity strategies become more robust and challenging, cybercriminals are mutating cyberattacks to be more evasive. Recent studies have highlighted the use of social engineering by criminals to exploit the human factor in an organization’s security architecture. Social engineering attacks exploit specific human attributes and psychology to bypass technical security measures for malicious acts. Social engineering is becoming a pervasive approach used for compromising individuals and organizations (is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 73 publications
1
31
0
Order By: Relevance
“…The results highlighted the important implications of increasing literacy in relation to cyber security. Siddiqi et al [40] suggested methods to counter SECA and concluded that training and educating individuals about cybersecurity measures and SECA is the top priority. With greater knowledge of the risk of attacks, a person can be more alert to SECAs.…”
Section: Discussionmentioning
confidence: 99%
“…The results highlighted the important implications of increasing literacy in relation to cyber security. Siddiqi et al [40] suggested methods to counter SECA and concluded that training and educating individuals about cybersecurity measures and SECA is the top priority. With greater knowledge of the risk of attacks, a person can be more alert to SECAs.…”
Section: Discussionmentioning
confidence: 99%
“…Yeo-Johnson [38] can be denoted as (5). Where 'j' represents feature attributes, 'λ' can be a R, and λ =1 gives the identity conversion.…”
Section: B Data Transformationmentioning
confidence: 99%
“…As per recent surveys, the reported cyberattacks in 2021 were approximately 5.1 billion [3] [4]. The reports also indicate a surge in sophisticated and high-impact cyberattacks on critical infrastructure globally [4] [5]. Understandably, such a high number of cyberattacks indicate the need for enhancement in network security approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [8] used a modern approach to classify social engineering attacks based on the technique and the influence tactic that was employed. Furthermore, the authors mapped several types of attacks to various human vulnerabilities.…”
Section: Related Workmentioning
confidence: 99%
“…The difference between them lies in the fact that in compliance, a direct request is used to force a change in someone's behavior while in 'persuasion,' we are sending a message to force someone to change his/her behavior because of the message reception. Additionally, in [8], the authors further elaborate on influence methodologies, where they present the following categories: social influence, persuasion, attitude and behavior, trust and deception, language, and reasoning, countering social engineering-based cyberattacks, and machine learning-based countermeasures. Moreover, they classified the persuasion method into distinct types of persuasion: similarity, distraction, curiosity, and persuasion using authority.…”
Section: The Proposed Cse-pucmentioning
confidence: 99%